The Filipino primitive : accumulation and resistance in the American museum - See, Sarita Echavez (New York : New York University Press, 2017)
Nowhere can we appreciate so easily the intertwined nature of the triple forces of knowledge accumulation-capital, colonial, and racial-than in the imperial museum, where the objects of accumulation remain materially, visibly preserved. Sarita See maintains that it is this material collection of artifacts associated with the racial, colonial primitive that forms the foundation of American knowledge production. The Filipino Primitive takes Karl Marx's concept of "primitive accumulation, " usually conceived of as an economic process for the acquisition of land and the extraction of labor, and argues that we also must understand it as a project of knowledge accumulation. Taking us through the Philippine collections at the University of Michigan Natural History Museum and the Frank Murphy Memorial Museum, also in Michigan, See reveals these exhibits as both allegory and real case of the primitive accumulation subtending imperial American knowledge, just as the extraction of Filipino labor contributes to American capitalist colonialism. With this understanding of the Filipino foundations of the development of an American accumulative drive toward power and knowledge, we can appreciate the value of Filipino American cultural producers like Carlos Bulosan, Stephanie Syjuco, and Ma-Yi Theater Company who have created incisive parodies of an accumulative epistemology, even as they articulate powerful alternative, anti-accumulativesocial ecologies.
Introduction : accumulating the primitive -- Part I. The archive : dispossession by accumulation -- Part II. The repertoire of dispossession -- Conclusion : accumulation now and then.
Includes bibliographical references and index.
Keywords: MATERIAL CULTURE -- PHILIPPINES -- HISTORY